2011
DOI: 10.1016/j.jalz.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease Management Guideline: Update 2008

Abstract: The Guideline recommendations provide a framework to inform and improve medical care for AD by primary health care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 52 publications
0
26
0
1
Order By: Relevance
“…Previous crosssectional studies indicate that up to 44% of individuals with AD or dementia have sleep disturbances (Vitiello and Borson, 2001;Lyketsos et al, 2002). The first-line treatment of sleep problems for individuals with AD are nonpharmacological, including sleep hygiene practices, stimulation during the day, reduction of excessive stimulation, and/or noise in the evening (Segal-Gidan et al, 2011). Many clinical care guidelines alleviate the importance of nonpharmacological approaches (Rabins et al, 2007;Finnish Medical Society Duodecim, Helsinki, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous crosssectional studies indicate that up to 44% of individuals with AD or dementia have sleep disturbances (Vitiello and Borson, 2001;Lyketsos et al, 2002). The first-line treatment of sleep problems for individuals with AD are nonpharmacological, including sleep hygiene practices, stimulation during the day, reduction of excessive stimulation, and/or noise in the evening (Segal-Gidan et al, 2011). Many clinical care guidelines alleviate the importance of nonpharmacological approaches (Rabins et al, 2007;Finnish Medical Society Duodecim, Helsinki, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The list of components in the text box is summarized from multiple guidelines published over the past 15 years and these components are reflected in the content of recently tested models of care; these key components are rather consistent across guidelines and these components have changed little over time. (4043)…”
Section: Basic Components Of Best Practice Modelsmentioning
confidence: 99%
“…The steps include a description of the behavior (D) that includes timing, location, people involved, and detailed characteristics of the behavior. Investigation of causes (I) addresses the patient, caregiver, and environmental factors involved and includes medical sources that should be ruled out especially in an acute onset where they are commonly implicated [53,54]. Creating a plan (C) involves development of targeted strategies to address the behavior and underlying causes.…”
Section: Frameworkmentioning
confidence: 99%
“…Several professional organizations have suggested that drug therapy should be used only after the failure of non-pharmacological strategies or in cases of grave danger or distress [26,54,56] and that these strategies should be specifically targeted to stage of dementia [57]. For the purpose of discussion, we have divided these strategies into categories of environmental, caregiver, and behavioral approaches.…”
Section: Non-pharmacological Strategiesmentioning
confidence: 99%